Migration as a human affair: Integrating individual stress thresholds into quantitative models of climate migration. Issue 93 (March 2019) - Adams, Helen; Kay, Susan
Highlights: Residential satisfaction and mobility potential determine thresholds to migrate. Individual migration thresholds determine timing of climate-related depopulation. Increases in exposure to coastal hazard due to sea level rise occur non-uniformly. Early migration expected in Kanthaltali due to high mobility and hazard exposure. Late migration expected in Aslampur due to low mobility and low hazard exposure. Abstract: Sea level rise will expose millions of people to increasing coastal hazards and eventual land loss. Thus, it is important to understand how residents will make decisions about whether and when to move away with increasing exposure. Historically, non-material dimensions of human decision-making have been missing from quantitative modelling of migration under environmental change. Here, we use behavioural migration theory and the concept of an inherent mobility potential to define individual stress thresholds, represented in the tension between mobility potential and residential satisfaction. We further suggest that migration as an outcome is determined by psychological propensity to move, and that levels of capital act to modulate, rather than determine, migration responses, their timing and outcome. Using the southwest coast of Bangladesh as our case study, we quantify these characteristics using the results of a 1500 household social survey and define an exposure index based on projections of sea surface height drawn from a physical model. Aggregating data to the village level, we are able to identify place-specific mobility responses; for example, locations where high mobility characteristics are associated with high exposure and thus migration may occur earlier in response to increasing coastal hazard. By advancing theory on individual thresholds and demonstrating that complex human characteristics can be usefully quantified, we further the ability of such characteristics to be included in modelling approaches. The empirical results contribute to debates on immobility under climate change, and decision-making on the most appropriate adaptive responses to protect multi-dimensional well-being of climate-vulnerable people.